IMPLEMENTATION OF NEW TOOLS AND METHODS FOR INCREASING THE LEVEL OF CYBER SECURITY OF CRITICAL INFRASTRUCTURE OBJECTS - Davydiuk, Andrii (Ukrainian Information Security Research Journal, 2023)
Existing methods and means of ensuring cyber security of critical information infrastructure objects, developed on the basis of international standards and best practices, are quite effective in peacetime conditions, but do not take into account the hybrid nature of war, in which new threats appear, in particular, such as physical destruction , capture by the enemy, the lack of possibility of constant monitoring and control, limitations in defense resources and available personnel, problems in the supply of recovery equipment, interruptions in information exchange processes, the need for frequent changes in operating conditions, dynamic growth in the number and quality of cyber-attacks, etc., due to which their efficiency drops significantly. In view of this, there is a need to develop new and improve existing methods and means of cyber protection in order to increase the level of cyber security of critical infrastructure. The safety of the population and the performance of combat tasks by the troops depend on ensuring the cyber security of critical information infrastructure facilities as an integral part of critical infrastructure facilities.